2014
DOI: 10.1111/1556-4029.12540
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Tooth Crown Measurements in the Assessment of Ancestry

Abstract: As the hardest tissue in the body, teeth have the potential to offer a wealth of biological information to the forensic anthropologist, which can include the assessment of ancestry. Using a large data set of dental measurements, the efficacy of mesiodistal and buccolingual tooth dimensions to discriminate between broad, geographically based groups is explored. A general pattern is identified: African populations have the largest teeth, Asians possess teeth of intermediate size, and Europeans have the smallest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
5
34
1
1
Order By: Relevance
“…Although the application of anterior teeth measurements in forensic dentistry has been documented extensively, future efforts are needed to establish a common national or global database to assist in individual, gender, and ancestry identification. [51][52][53] This objective is beyond the scope of this study and should be planned as a future research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the application of anterior teeth measurements in forensic dentistry has been documented extensively, future efforts are needed to establish a common national or global database to assist in individual, gender, and ancestry identification. [51][52][53] This objective is beyond the scope of this study and should be planned as a future research.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of dental morphology, for example, Pilloud et al 40 showed that external tooth crown measurements varied sufficiently among populations to be used as an additional tool in forensic anthropology for the assessment of ancestry. Furthermore, none of these studies have been done on South African individuals, whereas population affinity may influence the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, none of these studies have been done on South African individuals, whereas population affinity may influence the parameters. In terms of dental morphology, for example, Pilloud et al 40 showed that external tooth crown measurements varied sufficiently among populations to be used as an additional tool in forensic anthropology for the assessment of ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Odontometric methods are widely used in anthropology. They become a part of ethnological, archaeological, genetic, gender, racial and other studies (Zubov, 1973;Townsend et al, 2012;Pilloud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%